2020
DOI: 10.1371/journal.pone.0241870
|View full text |Cite
|
Sign up to set email alerts
|

Non-consumptive effects stabilize herbivore control over multiple generations

Abstract: Understanding the factors that influence predator-prey dynamics requires an investigation of oscillations in predator and prey population sizes over time. However, empirical studies are often performed over one or fewer predator generations. This is particularly true for studies addressing the non-consumptive effects of predators on prey. In a previous study that lasted less than one predator generation, we demonstrated that two species of parasitoid wasps additively suppressed aphid populations through a comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 52 publications
(81 reference statements)
0
9
0
Order By: Relevance
“…For example, the presence of Coccinella septempunctata increased the spread of BYDV at 7 days but had no significant effect after 14 days (Smyrnioudis et al 2001). An increase in the duration of the monitoring is particularly relevant for parasitoids (Ingerslew and Finke 2020). Indeed, unlike predators, there is no immediate consumption of the prey and the death of the parasitized host may only occur after a long period of time.…”
Section: -Conservation Biological Control and Management Of Vector-bo...mentioning
confidence: 99%
“…For example, the presence of Coccinella septempunctata increased the spread of BYDV at 7 days but had no significant effect after 14 days (Smyrnioudis et al 2001). An increase in the duration of the monitoring is particularly relevant for parasitoids (Ingerslew and Finke 2020). Indeed, unlike predators, there is no immediate consumption of the prey and the death of the parasitized host may only occur after a long period of time.…”
Section: -Conservation Biological Control and Management Of Vector-bo...mentioning
confidence: 99%
“…However, field studies with annual plants have shown that parasitism and non-consumptive effects of parasitic wasps can contribute up to 80% in reducing damage by herbivorous insects (Fig. 2), which contributes to promoting plant biomass production, and improving plant fitness [83][84][85][86]. While the effects of attracting parasitoids on net herbivory can be unclear, studies have shown that avian predators are also attracted by HIPVs emitted by trees [87,88].…”
Section: Effects Of Bvoc-mediated Communication On Herbivores In Fore...mentioning
confidence: 99%
“…In addition to directly dampening competitive interactions by preying on herbivores (4), predators and parasitoids may also affect the outcome of plant-mediated interactions among herbivores (5)(6)(7). With their presence, predators create a landscape of fear that causes changes in herbivore behaviour such as shifts in the intensity of feeding and feeding position of herbivores (7)(8)(9). Parasitoids that use phytophagous insects as host for their offspring even manipulate host physiology and behaviour that results in altered interactions of the phytophagous host with the food plant (10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%